Contribution of hospitals and clinical services to global warming: protocol for a scoping review - Waldo Merino-Urrutia; Claudio Cárcamo-Fuentes; Mauricio Peña; María José Martinez-Zapata (BMJ Open)
Introduction Climate change is one of the greatest threats to public health today, placing considerable pressure on the healthcare sector. During patient care processes, hospital facilities contribute to greenhouse gas emissions through the use of greater resources and higher energy consumption. Consequently, there is growing interest among researchers, universities, organisations and governments to study the impact of the healthcare sector on the environment and to develop strategies to mitigate its effects. The aim of this scoping review is to determine the extent and nature of current literature on global warming from hospitals and clinical services, and ways in which they contribute to its effect. Planning and execution of future research are possible once those areas with existing gaps are identified.Methods and analysis A broad literature search will be carried out to illustrate the ways in which hospitals and clinical services, processes and activities contribute to climate change. Our protocol was drafted using the Preferred Reporting Items for Systematic reviews and Meta-Analyses extension for Scoping Reviews. The final protocol was registered prospectively with the Open Science Framework. All identified studies indexed in Medline, Scopus and Embase will be examined.Ethics and dissemination This project is literature-based research; therefore, it does not require ethical approval. The results will be presented to researchers as well as policymakers in this particular area, via conferences, webinars, podcasts and online events. A peer-reviewed publication will be submitted to specific journals of interest.